Community Service Of Religiusity, Spirituality, And Individual Character In Work In The Age Of Society 5.0 - Shaddiq, Syahrial; Khuzaini, Khuzaini; Irpan, M.; Saputra, M Rizeki Yuda; Firdaus, Agus; Salim, Agus (Journal of Humanity Dedication, 2023)
This study aims to explore the relationship between religiosity, spirituality, and individual character in the work context. Religiosity and spirituality have an important role in shaping individual values and beliefs, which can influence their behavior and character in the work environment in the era of society 5.0. Individual character includes aspects of morality, ethics, integrity, responsibility, and other qualities that are relevant in the professional world. This study uses a qualitative approach by combining a comprehensive literature review and analysis of data from interviews with individuals with diverse work experiences. The results of the study show that religiosity and spirituality can provide a strong moral basis and influence the way individuals interact with colleagues, superiors, and customers. Internalized values through individual religious or spiritual practices can shape ethical attitudes and behavior, reflect integrity, and strengthen responsibility towards work. In addition, this study also found that religiosity and spirituality can enrich individual work experiences by providing a sense of purpose, meaning, and balance in professional life. Individuals who have a deep understanding of religious values or spirituality tend to be more satisfied in their jobs and have a more positive perception of the organization they work for. However, this research also underlines that aspects of religiosity and spirituality do not always have a positive impact in the work context. Some individuals may use their beliefs as an excuse to justify unethical or discriminatory behavior, which can create tension or conflict in the workplace. In addition, individual religious or spiritual views may differ, and these differences may affect interpersonal relationships in the work environment. The results of this study provide a better understanding of the importance of considering aspects of religiosity, spirituality, and individual character in the work context. The implications of this research include the importance of organizations promoting an inclusive work climate and respecting the diversity of individual beliefs, as well as providing space for individuals to express their religious or spiritual values in a positive way and in line with universal ethical and moral principles.